Suppression and azimuthal anisotropy of prompt and nonprompt J / ? production in PbPb collisions at ?sNN=2.76TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
The nuclear modification factor RAA and the azimuthal anisotropy coefficient v2 of prompt and nonprompt (i.e. those from decays of b hadrons) J / ? mesons, measured from PbPb and pp collisions at sNN=2.76TeV at the LHC, are reported. The results are presented in several event centrality intervals and several kinematic regions, for transverse momenta pT> 6.5 GeV/c and rapidity | y| < 2.4 , extending down to pT= 3 GeV/c in the 1.6 < | y| < 2.4 range. The v2 of prompt J / ? is found to be nonzero, but with no strong dependence on centrality, rapidity, or pT over the full kinematic range studied. The measured v2 of nonprompt J / ? is consistent with zero. The RAA of prompt J / ? exhibits a suppression that increases from peripheral to central collisions but does not vary strongly as a function of either y or pT in the fiducial range. The nonprompt J / ?RAA shows a suppression which becomes stronger as rapidity or pT increases. The v2 and RAA of open and hidden charm, and of open charm and beauty, are compared. © 2017, CERN for the benefit of the CMS collaboration.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2017). Suppression and azimuthal anisotropy of prompt and nonprompt J / ? production in PbPb collisions at ?sNN=2.76TeV. European Physical Journal C, 77(4). doi:10.1140/epjc/s10052-017-4781-1